Evaluation of variables influencing success and complication rates in canine total hip replacement: results from the British Veterinary Orthopaedic Association Canine Hip Registry (collation of data: 2010–2012). (1st July 2017) - Henderson, Elisabeth R.; Wills, Andrew; Torrington, Andrew M.; Moores, Andy P.; Thomson, David; Arthurs, Gareth; Brown, Gordon; Denny, Hamish R.; Scott, Harry W.; MacQueen, Ian; Dunne, James; Onyett, Jeremy; et al.
Abstract : The objective of this study was to assess the variables associated with complications of total hip replacement (THR) and report owner‐assessed outcomes. Entries into the British Veterinary Orthopaedic Association‐Canine Hip Registry (BVOA‐CHR) between September 2011 and December 2012 were reviewed separately and in conjunction with previous data (January 2010–August 2011). An outcomes assessment questionnaire was used to collect data from owners. Incidences of surgeon‐reported and owner‐reported complications were 8.2 per cent and 4.3 per cent, respectively. THR using the BioMedtrix BFX cup/stem prosthesis had a greater incidence of complications compared with THR using the BioMedtrix CFX cup/stem prosthesis (P=0.002); complications were 4.48 times more likely when using the BioMedtrix BFX cup/stem prosthesis versus the BioMedtrix CFX cup/stem prosthesis. THR using the BioMedtrix BFX cup/stem prosthesis had a higher incidence of complications compared with THR using a hybrid prosthesis (BioMedtrix BFX cup/CFX stem, BioMedtrix CFX cup/BFX stem) (P=0.046); complications were 2.85 times more likely when using the BioMedtrix BFX cup/stem prosthesis versus a hybrid prosthesis. In 95 per cent of cases, owner satisfaction with the outcome of THR was 'very good' or 'good'. Complication rates from the BVOA‐CHR are similar to previous studies. The data suggest that prosthesis type is associated with complication rate, with BioMedtrix BFX (circa 2012) having a high short‐term complication rate.